PENGARUH PENGGUNAAN METODE DISCOVERY LEARNING BERMEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR MENGGAMBAR BENTUK SISWA KELAS VII SMP N 2 PADANG GANTING - Drs. Abd. Hafiz, M.Pd., Regi Firga Ningsih, Dr. Ramalis Hakin, M.Pd., (Jurusan Seni Rupa FBS UNP Padang, 2016)
The study aims to look at the effect of learning outcomes draw shapes using discovery learning methods bermedia audio-visual class VII SMP N 2 Padang Ganting. This type of research is quantitative experimental method. Data research is test result score draw shapes by using audio-visual discovery mediated learning and using the conventional method of Class VII student of SMP N 2 Padang Ganting.The results of the study, it was concluded that the results of learning to draw shapes by using audio-visual discovery learning bermedia the experimental class is higher than the control class using conventional methods class VII SMP 2 Padang Ganting.Kata kunci: metode discovery learning, media audio visual, hasil menggambar bentuk.